PENGABDIAN KEPADA MASYARAKAT “TERASDigital Peguyangan Kaja” (Transformasi Era Layanan Administrasi Menuju Sistem Digital Desa Peguyangan Kaja Melalui Tanda Tangan Elektronik) - Dana, Gde Wikan Pradnya; Yuniari, Ni Putu Widya; Aryastana, Putu; Kumara, I Made Surya; Bhaskara, Made Adi; Darma, I Gede Wira; Raharja, I Kadek Agus Wahyu (Jurnal Pelayanan dan Pengabdian Masyarakat (Pamas), 2025)
Information technology within organizations, companies, and government institutions today plays a very significant role. However, the implementation of information technology in Indonesia still faces challenges in terms of efficiency and effectiveness, particularly in the village governance sector. On July 9, 2024, the Computer Engineering Faculty at Warmadewa University conducted a Community Service Program titled "TERAS Digital Peguyangan Kaja," which involved outreach and training to maximize the use of electronic signatures, evaluated using SWOT analysis. This program offers benefits such as the effectiveness and efficiency of public services. The implementation of electronic signatures is hindered by infrastructure issues and social resistance, necessitating outreach, intensive training, and infrastructure improvements. This community service program, in collaboration with the Denpasar City Communication and Information Agency (Diskominfo). This activity involved 25 participants consisting of village officials and service implementers, as well as representatives from the Denpasar City Communication and Information Office (Diskominfo). The evaluation of activities was carried out using SWOT analysis, involving socialization, training, and mentoring to implement the use of electronic signatures. evaluation using SWOT analysis. The implementation of socialization and training has increased the digital literacy of the community and village officials, increasing efficiency and effectiveness in solving the problems of the people of Peguyangan Kaja Village when the party whose signature is required by the village apparatus is in the way. . Although electronic signature technology has just begun to be implemented, there are technical obstacles and infrastructure limitations in Peguyangan Kaja Village that need to be overcome to ensure that this technology functions optimally and is accepted by the community. Future plans focus on improving the overall implementation of electronic signatures and increasing socialization to ensure the sustainability and effectiveness of the program. Keywords: Electronic Signatures, Socialization, Training, SWOT Analysis\